The Implementation of the C3T Method Using Interactive Tests to Enhance Arabic Language Teaching at Jalaluddin Rumi Junior High School, Jember - Muhammad Badrus Salam; Mokhammad Miftakhul Huda; Asep Maulana; Mohammed Saeed (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the integration of the C3T method and Kahoot-based interactive tests to improve the quality of Arabic language learning assessment at SMP Jalaluddin Rumi Junior High School, Jember. It addresses the limited use of formative and interactive assessment in Arabic instruction, where conventional evaluation methods remain dominant and less effective in developing speed, accuracy, and collaboration. The study employed Classroom Action Research based on the Kemmis and McTaggart model in two cycles involving 21 seventh-grade students divided into seven groups. Data were collected through tests, observation, and documentation, and analyzed using descriptive quantitative and qualitative techniques within a formative assessment framework. The findings show continuous improvement in both learning process and outcomes. Student participation, collaboration, and engagement increased from Cycle I to Cycle II, along with more effective classroom interaction. Quantitatively, the average group score improved from 6.78 to 7.71 across all groups. These results indicate that the integration of the C3T method with interactive assessment contributes to a more formative, objective, and efficient evaluation system through real-time feedback, time constraints, and collaborative learning. The novelty lies in systematically combining C3T with interactive digital formative assessment that emphasizes speed, accuracy, collaboration, and immediate feedback. In conclusion, this integration contributes to improving Arabic language assessment quality, although its implementation is influenced by technological access, classroom management, and student discipline.